A one-year study of human milk oligosaccharide profiles in the milk of healthy UK mothers and their relationship to maternal FUT2 genotype. (15th June 2021) - Durham, Sierra D; Robinson, Randall C; Olga, Laurentya; Ong, Ken K; Chichlowski, Maciej; Dunger, David B; Barile, Daniela
Abstract: Human milk oligosaccharides (HMOs) are indigestible carbohydrates with prebiotic, pathogen decoy and immunomodulatory activities that are theorized to substantially impact infant health. The objective of this study was to monitor HMO concentrations over 1 year to develop a long-term longitudinal dataset. HMO concentrations in the breast milk of healthy lactating mothers of the Cambridge Baby Growth and Breastfeeding Study (CBGS-BF) were measured at birth, 2 weeks, 6 weeks, 3 months, 6 months and 12 months postpartum. HMO quantification was conducted by high-performance anion-exchange chromatography with pulsed amperometric detection using a newly validated "dilute-and-shoot" method. This technique minimizes sample losses and expedites throughput, making it particularly suitable for the analysis of large sample sets. Varying patterns of individual HMO concentrations were observed with changes in lactation timepoint and maternal secretor status, with the most prominent temporal changes occurring during the first 3 months. These data provide valuable information for the development of human milk banks in view of targeted distribution of donor milk based on infant age. Maternal FUT2 genotype was determined based on identification at single-nucleotide polymorphism rs516246 and compared with the genotype expected based on phenotypic markers in the HMO profile. Surprisingly, two mothers genotyped as secretors produced milk that displayed very low levels of 2′-fucosylated moieties. This unexpected discrepancy between genotype and phenotype suggests that differential enzyme expression may cause substantial variation in HMO profiles between genotypically similar mothers, and current genotypic methods of secretor status determination may require validation with HMO markers from milk analysis.